Dawn Manco
MA 502 Project
1. Show that the set of polynomials
,
,
,...,
,... where
satisfy the identity (***)
. In semigroup parlance, this says that the function
is an isomorphism between the semigroup
of all polynomials
under composition and the semigroup
of non-negative integers under mulitplication.
> p[0]:=1;
> p[1]:=x;
> for r from 2 to 6 do p[r]:=expand(2*x*p[r-1]-p[r-2]) od;
This came from a previous worksheet that we did and saved. (The day we made the graph 9-9-99)
> p2p3:=expand(subs(x=p[3],p[2]));
> p3p2:=expand(subs(x=p[2],p[3]));
> p2p3-p3p2;
> p[6]-p2p3;
> p[6]-p3p2;
So we see that for the case n=2, m=3 and n=3, m=2 they are the same as
.
> p[n]:= 2*x*(p[n-1]) - p[n-2];
> p[m]:= 2*x*(p[m-1]) - p[m-2];
> p[m*n]:=2*x*(p[m*n-1]) - p[m*n-2];
> p1p2:= expand(subs(x=p[2],p[1]));
> p2p1:=expand(subs(x=p[1],p[2]));
> p2p1 - p1p2;
> p1p2 - p[2];
> p2p1 - p[2];
> p1p3:= expand(subs(x=p[3],p[1]));
> p3p1:= expand(subs(x=p[1],p[3]));
> p1p3 - p[3];
> p3p1 - p[3];
> p1p3 - p3p1;
> pmp1:= expand(subs(x=p[1],p[m]));
> p1pm:= expand(subs(x=p[m],p[1]));
> p1pm - pmp1;
> p1pm - p[m];
> pmp1 - p[m];
As we have seen through these examples, the polynomials commute.
Now we must prove that
. This can be done by using
to satisfy the identity.
> restart;
> P[n]:= expand(cos(n*arccos(x)));
> for n from 0 to 6 do P[n]:= expand(cos(n*arccos(x))) od;
Through examples, we have shown that P[n] equals p[n] for n = 0..6. Now, we must use mathematical induction to prove the P[n] = p[n] for all n.
(I don't know how to execute this as a maple worksheet so I am going to type it out as text in blue.)
Fine. I prefer that anyway.
=
=
=
, for all n given that
and
by definition.
In order to prove by induction
that
for all n
, we must use three steps.
1) Show that the formula is true for
.
and n = 0
by definition
= cos(0) = 1
so
by definition.
=
2) Assume the formula is true for
.
and n-1 (this is important, see below)
=
3) Prove that the formula is true for
. In doing so will prove the formula to be true for all
.
(this is known)
=
=
{distribution}
=
{substitution with trig Id. (**)}
=
{substitution: cos(arccos(x)) = x}
=
{substitution: P[n] = cos(n*arccos(x))}
=
-
*[
] {sub with trig Id. (***)}
=
-
*[
] {simplify}
=
-
*[
] (substitution: definition of P[n]}
=
-
*[
] {multiply by 2 to cancel 1/2}
=
{simplify}
{subtract P[n+1} from both sides}
=
(by assumption, note that we need to assume p[n-1] = P[n-1] also)
(**)
(***)
=
*[
]
So
you have a nice proof, modulo the inserted steps.
QED
We need to prove that
. We now see that
satisfies the identity. Now we can use
to prove
.
> restart;
> p[n]:=cos(n*arccos(x));
> p[m]:=cos(m*arccos(x));
We know by definition that
. So will
?
> pmpn:=expand(subs(x=p[n],p[m]));
We know from our knowledge of trigonometry that
, so
=
=
.
So, in conclusion,
does infact equal
.